The reality of volunteerism at Imam Muhammad Bin Saud Islamic University from the viewpoint of students of the Faculty of Social Sciences - Al- Qahtani, Ibrahim Faraj Al- Khanfari (Journal of Educational and Psychological Sciences, 2019)
The study aimed to recognize the reality of volunteerism at Imam Muhammad Bin Saud Islamic University from the viewpoint of students of the Faculty of Social Sciences, and identify the administrative obstacles facing the management of volunteer action, and recognize the proposals that the sample of the study see to develop the management of Volunteering at the University. The researcher used the Survey approach to achieve the aims of the study, and he used the questionnaire as a tool for study, which was applied to a simple random sample consisting of (370) students from the Faculty of Social Sciences at Imam Muhammad bin Saud Islamic University, In Saudi Arabia. The study revealed a number of results, the most important of them are: That the rating of the reality of the management of voluntary action at the Imam Muhammad bin Saud Islamic University came in a medium degree and that there is a high degree of agreement among the sample of the study on the obstacles facing the administration of volunteer action at Imam Muhammad bin Saud Islamic University, The study presented several recommendations, the most important of them are: Attach the students to programs for training volunteers before they are assigned to work, and the need to establish administrative units concerned with volunteer work in college.